2020
DOI: 10.3390/en13020465
|View full text |Cite
|
Sign up to set email alerts
|

Development of Experimental Apparatus for Fire Resistance Test of Rechargeable Energy Storage System in xEV

Abstract: To secure the safety of xEV (all types of electrical vehicles), the United Nations released Global Technical Regulation No. 20, "Global Technical Regulations on the EVS (Electric Vehicle Safety)" in March 2018. The fire resistance test of the rechargeable energy storage system (REESS) describes an experimental procedure to evaluate the safety performance-specifically, whether passengers would have sufficient time to escape from the xEV before the explosion of the battery in a fire. There are two options for co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Safety is also an important aspect of power generation [17]. Intensive investigation is needed not only for the case of the generation itself but also for the case of energy storage [18]. Jung et al [18] focused their investigation on the development of an experimental apparatus for the fire resistance testing of batteries, with a primary focus on electric vehicles (xEVs) [18].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Safety is also an important aspect of power generation [17]. Intensive investigation is needed not only for the case of the generation itself but also for the case of energy storage [18]. Jung et al [18] focused their investigation on the development of an experimental apparatus for the fire resistance testing of batteries, with a primary focus on electric vehicles (xEVs) [18].…”
mentioning
confidence: 99%
“…Intensive investigation is needed not only for the case of the generation itself but also for the case of energy storage [18]. Jung et al [18] focused their investigation on the development of an experimental apparatus for the fire resistance testing of batteries, with a primary focus on electric vehicles (xEVs) [18]. The study concluded that the developed rig, consisting of LPG fired Bunsen burners, could be effectively used in the fire resistance testing of various batteries [18].…”
mentioning
confidence: 99%